CAREER PLATEAU DI PENGADILAN NEGERI/NIAGA/HUBUNGAN INDUSTRIAL/TIPIKOR SEMARANG: Faktor Penyebab dan Dampaknya Terhadap Kinerja - Banar Priyantoro, 11 52.02 0060 (Students Journal of Economic and Management, 2013)
The research objective was to identify the factors that lead to career plateau, to analyze the influence of these factors on career plateau and to analyze the influence of career plateau on employee performance Pengadilan Negeri Semarang Population is used as the object of all employees at the Pengadilan Negeri Semarang was done by purposive sampling techniques, criteria respondents were employees were civil servants in the State Court / Commercial / Industrial Relations / Semarang Corruption Court. Judge and Judge Candidates not meeting criteria for the respondents as their career path is clear. Likewise, temporary employees are not included because they do not qualify for the civil responders. So the number of samples in this study were 111 respondents. Analysis tools used in this study using linear regression. Results from the study include: (1). Supervisor support negatively affect the career plateau, meaning the better the support the boss, it will lower the career plateau. (2). Job involvement negatively affect the career plateau, job involvement means the better, it will lower the career plateau. (3) Planning careers negatively affect the career plateau, meaning the better career planning, it will lower the career plateau. (4) Career opportunities negatively affect the career plateau, meaning the better career opportunities, it will lower the career plateau. (5) Career plateau negatively affect employee performance, meaning that the lower the career plateau, the more it will improve employee performance Keywords: supervisor support, job involvement, career planning, career opportunities, career plateau and employee performance